South American wheat markets and MERCOSUR - Díaz-Bonilla, Eugenio (International Food Policy Research Institute, 1997)
This paper analyzes the wheat market in South America, with a focus on MERCOSUR. It argues that wheat markets in South America have undergone significant changes over the last decade, driven by the world macroeconomic and agricultural cycle of the last quarter of the century, as well as specific economic and sectoral policies in the region. Latin America's economic environment is now characterized by fiscal constraints and greater price stability, market liberalization and trade openness. In this new setting, Argentina has consolidated its position as a net exporter, due to both increased production and stagnant or even declining consumption, while Brazil and the rest of South America, with opposite trends in production and consumption, are increasing their net imports of wheat.These supply and demand changes, along with greater trade liberalization, are reshaping trade patterns in the region, increasing Argentina's exports to Brazil and the rest of South America. This trade environment will continue to change due to the phasing in of WTO disciplines, and the possible expansion of regional trade agreements. Wheat trade issues that in the past focused prominently on export subsidies and trade practices of state trading enterprises may, in the future, be more related to sanitary and phytosanitary practices or to controversies linked to wheat flour and wheat-based manufactured goods, rather than to the primary product. Besides trade and agricultural sector policies affecting directly the primary sector, other aspects to be considered for future patterns in wheat production, consumption and trade, are the evolution of the milling, bakery, pasta and related industries in Brazil and Argentina, and different macroeconomic policies in both countries, particularly regarding exchange rate regimes."